Exploration of viewpoints in identification of gymnastic talent with the back hip circle - Tanaka, H.; Fujii, K.; Takeyama, Y. (American Journal of Sports Science, 2021)
In Japan, students attempt the back hip circle in physical education class in school. It is considered a simple teaching material with which children can experience feelings of achievement and pride. A major factor behind this is that schoolyards in Japan do not have an environment for gymnastics, equipped only with horizontal bars. Therefore, the path from horizontal bars to gymnastics may have been laid from that time. We applied the wavelet interpolation model to the accomplishment rate for the back hip circle in young children, and described the development curve of that accomplishment rate. We then considered the level of physical maturity associated with the accomplishment rate from the behavior of the development velocity curve, and investigated whether the back hip circle accomplishment rate on the horizontal bar was linked to identification of subsequent talent in gymnastics. The results showed that when the behavior of the accomplishment rate velocity curve was compared in boys and girls, the peak velocity in girls was already detected at around the age of 3-4, and maturity was clearly earlier. The ability to comply with a sequence of movements (sequence compliance ability) was examined only in young children, but girls were superior to boys in that ability and girls also had a higher accomplishment rate in the back hip circle. Thus, a close relationship between non-cognitive ability and the back hip circle accomplishment rate may be conjectured. The accomplishment rate curve for back hip circles shows a neural pattern, like the development curve for the 50-m dash, and is dependent on a neural pattern. Thus, performance in the back hip circle can be evaluated from an early stage, and since an element of gymnastics can be distinguished, it may be a barometer for judging gymnastics talent, including genetics. Abilities that show a neural development pattern have a high genetic component, and genetic traits are expressed from early childhood and are highly likely to trace until adulthood. Therefore, in such individuals the physical abilities of coordination, flexibility, quickness, balance, and endurance are superior, and the back hip circle is accomplished early. The possibility was shown this early accomplishment of the back hip circle and the conditions of short height and low body weight are very important information in talent identification for gymnastics.